Towards an understanding of regulating Cajal body activity by protein modification. Issue 6 (3rd June 2017) - Hebert, Michael D.; Poole, Aaron R.
ABSTRACT: The biogenesis of small nuclear ribonucleoproteins (snRNPs), small Cajal body-specific RNPs (scaRNPs), small nucleolar RNPs (snoRNPs) and the telomerase RNP involves Cajal bodies (CBs). Although many components enriched in the CB contain post-translational modifications (PTMs), little is known about how these modifications impact individual protein function within the CB and, in concert with other modified factors, collectively regulate CB activity. Since all components of the CB also reside in other cellular locations, it is also important that we understand how PTMs affect the subcellular localization of CB components. In this review, we explore the current knowledge of PTMs on the activity of proteins known to enrich in CBs in an effort to highlight current progress as well as illuminate paths for future investigation.